Ultraviolet degradation of procymidone – structural characterization by gas chromatography coupled with mass spectrometry and potential toxicity of photoproducts using in silico tests. (21st May 2013) - Rifai, Ahmad; Souissi, Yasmine; Genty, Christophe; Clavaguera, Carine; Bourcier, Sophie; Jaber, Farouk; Bouchonnet, Stéphane
<x xml:space="preserve">Abstract</x> RATIONALE Procymidone is a dicarboximide fungicide mainly used for vineyard protection but also for different crops. The structural elucidation of by‐products arising from the UV‐visible photodegradation of procymidone has been investigated by gas chromatography coupled with mass spectrometry. The potential toxicities of photoproducts were estimated by in silico tests. METHODS Aqueous solutions of procymidone were irradiated for up to 90 min in a self‐made reactor equipped with a mercury lamp. Analyses were carried out on a gas chromatograph coupled with an ion trap mass spectrometer operated in electron ionization and methanol positive chemical ionization. Multistage collision‐induced dissociation (CID) experiments were performed to establish dissociation pathways of ions. Toxicities of byproducts were estimated using the QSAR T.E.S.T. program. RESULTS Sixteen photoproducts were investigated. Chemical structures were proposed mainly based on the interpretation of multistage CID experiments, but also on their relative retention times and kinetics data. These structures enabled photodegradation pathways to be suggested. Only three photoproducts remain present after 90 min of irradiation. Among them, 3, 5‐dichloroaniline presents a predicted rat LD50 toxicity about ten times greater than that of procymidone. CONCLUSIONS 3, 5‐Dichloroaniline is the only photoproduct reported in previous articles. Eight by‐products among the sixteen characterized might be as toxic, if not more, than procymidone itself considering the QSAR‐predicted rat LD50. Copyright © 2013 John Wiley & Sons, Ltd.